Procedimentos analítico comportamentais no treino de AVDS e AIVDS de crianças e adolescentes com TEA: uma revisão sistemática da literatura - ROCHA, Larissa Monteiro (2023)
Autism Spectrum Disorder (ASD) causes a number of impairments that make it difficult for children to learn in a variety of abilities, including Activities of Daily Living (ADLs) and Instrumental Activities of Daily Living (IADLs). Whereas the training of ADLs and IADLs has been the responsibility of the Occupational Therapist, and for decades the effectiveness of procedures based on Applied Behavior Analysis has been proven in treating this population, including teaching these skills, the present work aimed to review the studies on behavioral analytical procedures used in the training of ADLs and IADLs with children and adolescents within the autism spectrum. A systematic literature review was performed by consulting the search indexers in electronic databases. After applying the inclusion criteria, ten studies were analyzed from five categories. The results indicated that the procedures used were Video Modeling and Chaining and these proved to be effective and with possible potential to be implemented in the practice of Occupational Therapy to teach daily life skills for children and adolescents with ASD.